2015
DOI: 10.1155/2015/178947
|View full text |Cite
|
Sign up to set email alerts
|

Immune Evasion Strategies ofTrypanosoma cruzi

Abstract: Microbes have evolved a diverse range of strategies to subvert the host immune system. The protozoan parasite Trypanosoma cruzi, the causative agent of Chagas disease, provides a good example of such adaptations. This parasite targets a broad spectrum of host tissues including both peripheral and central lymphoid tissues. Rapid colonization of the host gives rise to a systemic acute response which the parasite must overcome. The parasite in fact undermines both innate and adaptive immunity. It interferes with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 99 publications
0
33
0
1
Order By: Relevance
“…Survival of T. cruzi in the host depends on it escaping from immune recognition and/or it evading immune effector mechanisms. Several studies revealed that proteins secreted by the protozoan in the bloodstream, glycosylphosphatidylinositol-mucins molecules present in the parasite surface, and the blockade of complement pathways are strategies used by T. cruzi to escape immune recognition and delay the progression of immune response ( 52 54 ). The capacity of the parasite to survive has been attributed to the suppression of immune responsiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Survival of T. cruzi in the host depends on it escaping from immune recognition and/or it evading immune effector mechanisms. Several studies revealed that proteins secreted by the protozoan in the bloodstream, glycosylphosphatidylinositol-mucins molecules present in the parasite surface, and the blockade of complement pathways are strategies used by T. cruzi to escape immune recognition and delay the progression of immune response ( 52 54 ). The capacity of the parasite to survive has been attributed to the suppression of immune responsiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of whether a cell is infected by viruses, bacteria, protozoa, or fungi, the pathogen in each case uses the immune system to modulate the response and, thereby, survive inside the cell. [163][164][165] Bacteria and protozoa One of the key issues arising from the discussion of this subject is understanding the response that PRRs can induce through the recognition of PAMPs of certain microorganisms. Classically, receptors such as those in the Toll family agglutinate a variable range from TLR1 to TLR13.…”
Section: Mechanisms Of Immune Evasion Used By Intracellular Pathogensmentioning
confidence: 99%
“…By a general mechanism known as colonization resistance (87)(88)(89), members of the gut microbiota are thought to antagonize pathogens. Production of bacteriocidins or peroxidases can inhibit or kill pathogenic bacteria.…”
Section: Figmentioning
confidence: 99%